Early years postgraduate surgical training programmes in the UK are failing to meet national quality standards: An analysis from the ASiT/BOTA Lost Tribe prospective cohort study of 2, 569 surgical trainees. (April 2018) - ,; ,; ,; Glasbey, James C.; Harries, Rhiannon L.; Beamish, Andrew J.; Gokani, Vimal J.; Mohan, Helen; Williams, Adam P.; Glasbey, James C.; Fleming, Simon; Williams, Adam P.; et al.
Abstract: Introduction: This study aimed to assess training of Senior House Officer-grade equivalent doctors in postgraduate surgical training or service (SHO-DIPST) in surgical specialties across the United Kingdom (UK), against nationally agreed Joint Committee on Surgical Training Quality Indicators (JCST QIs). Specific recommendations are made, with a view to improving quality of training, workforce retention and recruitment to Higher Surgical Training. Method: Prospective, observational, multicentre study conducted by the Association of Surgeons in Training, using the UK National Research Collaborative model. Any centres in the UK providing acute surgical services were eligible. SHO-DIPST with a permanent contract, on out-of-hours 'on-call rota' were included across four, one-week data capture periods (September to October 2016, February to March 2017). Adherence to five quality indicators was reported using descriptive statistics. P-values were calculated using Student's t-test for continuous data, with a 5% level of significance. Results: 2569 SHO-DIPST were included from all ten surgical specialties in 141 NHS trusts across all 16 Local Education and Training Boards in the UK. 960 SHO-DIPST were in registered 'training' posts (37.3%). The median number of SHO-DIPST per rota was 7.0 (IQR 5.0–9.0). Adherence to the five included JCST QIs ranged from 6.0 to 53.1%. Only four SHO-DIPST posts across the study population met all five JCST QIs (0.3%). The total number of training sessions was higher for those in registered training posts (p < 0.001), with significant specialty and regional variation. Conclusions: Only four early years postgraduate surgical training posts in the UK meet nationally approved minimum quality standards. Specific recommendations are made to improve training in this cohort and to bolster recruitment and retention into Higher Surgical Training. Highlights: Four early years postgraduate surgical training posts met national quality indicators. There exists significant inter-specialty and regional variation in surgical training. Half of doctors had no exposure to theatre or clinic during the study week. This is the first study to assess sessional activities against training quality standards. Significant efforts are required universally to improve training standards.